Teacher identity formation, socio-spatial representations and university autonomy : the complex case of a public university of Minas Gerais - Alves, Daniel Cardoso; Sampaio, Andrecksa Viana Oliveira (Universidade Estadual de Campinas, 2020)
This article aims to understand and analyze, in the context of teaching, the relational movement between identity formation and social representation of space. For this purpose, the case of the State University of Minas Gerais (UEMG) is used when the declaration of unconstitutionality of complementary law nº. 100/2007. The argument that permeates this study is that teacher identity formation results from an unstable process intrinsically associated with the socio-cultural appropriation of spaces. With this understanding, a theoretical approach was sought between the conceptions of teacher identity and socio-spatial representation, made possible by the conceptual deepening of the categories territory, place and culture. As methodological procedures, in addition to the bibliographic review, documentary research was adopted in order to understand narratives and discourses from documentary sources (administrative, journalistic and electronic). The analysis of the content of these sources allowed a better understanding of the productions of sense to the context investigated. Among other contributions, the study showed that, in the face of the constant "making" of the teacher identity, the unveiling of state actions and the teacher-subject's awareness of the processes related to this "making" are essential for a liberating identity formation and, consequently, for the consolidation of the university as a territory / place increasingly closer to its genuine mission of social institution.